The Role of Self-Regulated Learning in Physical Education and Sports. Α Review - Nikolaki Ευγενία; Koutsouba Μαρία; Venetsanou Φωτεινή; Likesas Γιώργος (Inquiries in Physical Education and Sport, 2016)
The aim of this paper was the critical review of up to now research regarding self-regulated learning in physical education and sports. In particular, the paper explores the way in which the multifactor process of self-regulation affects the motivational, emotional and behavioral learners’ skills. Based on the literature review, the significance of self-regulated learning in the development and performance of motor and sport skills is revealed, while its positive effect in learners’ motivation, as well as its correlation with more adaptable behavioral prototypes in physical education and sports is pointed out. It is showed that the design of appropriate educational program promotes self-regulated learning and that this promotion supports lifelong for health and quality life.